The Effect of Team Games Tournament (TGT) Model Toward Students Writing Skills of 11th Grade of SMAN 1 Bengkulu City - Yulia Juniarti; Ferri Susanto; Dedi Efrizal (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to investigate the effect of the cooperative learning method using the Team Games Tournament (TGT) model on students’ writing skills, specifically in writing analytical exposition texts for 11th-grade students at SMAN 1 Bengkulu City. The background includes several problems, such as some students not reaching the Minimum Completeness Criteria (KKM), difficulties in translating questions and writing English paragraphs due to limited vocabulary, differences in learning interest, and low student involvement in class discussions. This research used a quantitative approach with a quasi-experimental design involving two classes, the experimental and control class, each with 36 students. The instrument was a writing test consisting of pre-tests and post-tests. Data were analyzed using SPSS version 28. The results showed a significant effect of the TGT model on students’ writing skills, proven by the F test result with an F value of 56.782, greater than the F table value of 3.98, with an effect contribution of 44.8%. The findings indicate that the Team Games Tournament (TGT) model is effective in improving students’ ability to write analytical exposition texts in a structured, communicative manner, so it can be recommended as a learning model for teachers in teaching writing skills in the classroom.